Psychological Warfare as a Driving Factor in the Development of Military Strategy During the Gulf War 1990-1991 - Putra, Galih Adi; Wirajuda, Muhammad Hadianto; Risman, Helda (Advances in Social Sciences Research Journal, 2024)
This research explores the pivotal role of psychological warfare during the Gulf War (1990-1991), unraveling its transformative impact on the conflict’s psychological landscape. It aims to analyze the psychological warfare conducted by the US coalition to create favorable conditions for a major war, and the outputs of psychological warfare contribute as a driving factor in developing military strategy. The study employs literature studies by collecting data from historical documents and scholarly works. Propaganda, Deception, and Information Warfare emerge as adaptive tools within the evolving media landscape. Psychological operations strategically disrupt communication and influence perceptions by targeting both Enemy and Allied Forces. The study demonstrates the psychological impacts on military strategy through High-Level Decision-Making and the Integration of Psychological Factors into Strategic Planning. Military strategies exhibit adaptability through Flexible Tactics and Targeted Operations, dynamically responding to psychological outcomes. Communication and coordination, both within intelligence agencies and among allied forces, amplify the impact of psychological warfare by seamlessly integrating psychological strategies into broader military campaigns.